Urgensi Manajemen Humas Dalam Membangun Citra Pondok Pesantren di Masyarakat - Ghazali, Ziyadul Ifdhal (Al-Abshar: Journal of Islamic Education Management, 2024)
Public relations management is one of the many management functions in educational institutions that have vital roles and functions. Experts say that the success of educational institutions depends on the ability of public relations to build approaches and communication with the community. Islamic boarding schools are a traditional Islamic education system, cultural heritage and traditions of the Indonesian people. The establishment of Islamic boarding schools is usually on the basis of kiai initiatives that are welcomed by the community. This study wants to reveal the urgency of public relations management in Islamic boarding schools. This study used qualitative method with descriptive analysis. This study found that there are at least three reasons for the urgency of public relations management in Islamic boarding schools, namely; (1) Islamic boarding schools as social institutions, (2) the unique relationship between kiai-santri, (3) the central role of kiai in society, and (4) the demands of globalization